SPASIAL KETERJANGKAUAN RUMAH SAKIT TERHADAP KECELAKAAN DI JALAN BY PASS KOTA PADANG - Fahda Fadillah; Triyatno Triyatno; Endah Purwaningsih (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This Research aims; 1) know the pattern of a spread of points of traffic accident on the Road By Pass Padang City. 2) analyze the affordability of the hospital to the traffic location on The road By Pass Padang City. This method of research is descriptive with a quantitative approach. and the data used is secondary data and primary data. In obtaining the result of the pattern of location distribution point of the researcher using NNA (Nearest Neighbour Analysis) method, while to get results from the hospital range using the Service Area method. The results of this research show that the pattern of the spread of traffic accident spots on the Bypass Padang city is a pattern of clustered, it is known that the value of Nearest Neighbor Ratio is 0.20; The Z-score value is-, 18.16; And the p-value value is 0.00. Hospital coverage against the location of the traffic accident at the Bypass Padang City has a range of 100 m – 2000 m, of the three hospitals on the Bypass highway there are 112 incidents of affordable traffic accidents and 33 incidents of traffic accidents that are not reachable by the three hospitals.